Factors Affecting Customer Loyalty Through Satisfaction at UD. Sumber Makmur Banyuajuh Village, Kamal District - Ilham Zainia Rizkiyah; Aulia Dawam; Manah Tarman (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This research was conducted with the aim of understanding the effect of price, location, product and service quality on customer loyalty through satisfaction as an intervening variable at UD. Prosperous Source. The type of research used in this research is descriptive quantitative with nonprobability sampling and convenience sampling approaches. The sample used was 30 respondents as customers at the tofu factory. Data analysis techniques in this study used validity, reliability, classic assumption tests which consisted of normality tests, multicollinearity tests, and heteroscedasticity tests. multiple linear regression analysis test, coefficient of determination test, t test and F test. In analyzing the results of this study using the SPSS version 2023 application. The results of the research show that product and service quality has no effect on satisfaction; price, the effect of location on satisfaction; price, location, quality of products and services affect customer loyalty; satisfaction affects customer loyalty; price, location, product and service quality simultaneously affect customer loyalty through satisfaction.